The Urgency of Harmonizing Civil Inheritance Law with Digital Assets in the Indonesian Legal System - Nur Ali; Adang Djumhur Salikin; Kosim Kosim (JURNAL AKTA, 2025)
The development of digital technology has given rise to new types of non-physical wealth, such as cryptocurrency, e-wallets, social media accounts, and digital intellectual property. However, Indonesia's civil inheritance law system, which is based on the Burgerlijk Wetboek (Civil Code), does not explicitly regulate the status and mechanism of inheritance of such digital assets. The absence of specific regulations creates legal issues for heirs, ranging from difficulties in identification to obstacles in accessing the digital assets of the deceased. This study employs a normative and comparative legal approach by analyzing national legislation, inheritance practices in several countries such as the United States (RUFADAA), and theories of legal harmonization. The results of the study indicate that, conceptually, digital assets meet the criteria as legal objects that can be inherited because they have economic value and transferable ownership. However, the absence of explicit regulations in national law makes digital assets vulnerable to loss or improper distribution. Therefore, legal harmonization is an inevitability. Legal harmonization of inheritance regarding digital assets can be achieved through three main schemes. First, integrating digital assets into the list of inherited assets by explicitly including them in a will (testamentaire beschikking) or statement of assets. Second, establishing a mechanism for identifying and distributing digital assets involving notaries as legal actors and developing a national digital data system. Third, the formulation of technical regulations that grant legal access to heirs to the deceased's digital accounts and cryptocurrency wallets, accompanied by cross-border enforcement cooperation with global digital service providers. These three schemes are based on the principles of volledigheid van de nalatenschap, gerechtigheid (justice), and rechtszekerheid in Dutch law, and are in line with Nonet and Selznick's theory of responsive law, which encourages the adaptation of law to social and technological dynamics. The comprehensive reformulation of inheritance law provisions in the Civil Code is a strategic step in ensuring legal protection for heirs and addressing the challenges of digital inheritance in the information society era.